ELECTRONIC PERSONS IN CONTRACTS - Michele van Eck; Fafa Agbeko (Obiter, 2023)
Contemporary technological developments have already progressed far beyond the electronic and digital transactions recognised under the Electronic Communications and Transactions Act 25 of 2002 (ECTA). Internationally, there are calls for the regulation not only of robots and artificial intelligence (AI) but also of sophisticated automated electronic systems and AI that now have the capability to make self-sustainable decisions and exhibit human characteristics (conceptually referred to as electronic persons). The growing legal debate is whether such systems should be afforded equal (or similar) legal status to human beings and thereby have rights and be responsible for duties – that is, be afforded the mantle of legal personhood. Alternatively, should a different liability regime apply to these systems, their operators and creators? Europe has suggested both approaches. First, in 2016, the European Parliament’s Committee on Legal Affairs included recommendations to the Commission on Civil Law Rules on Robotics that suggested that electronic persons should in the future be recognised as entities having legal status and legal personality. Secondly, in 2020, the European Parliament made recommendations to the Commission on a Civil Liability Regime for Artificial Intelligence, which proposed liability structures for these systems, their operators and creators. If legal recognition were afforded, as initially suggested in 2016, this would constitute something fundamentally different from juristic persons and would have a direct influence on the way contracts are concluded and their consequences. This article explores the concepts of legal status and personality from the perspective of recognised contractual parties (natural and juristic persons), as well as that of a conceptual electronic person, which may manifest itself as either a passive electronic person (more akin to a useful tool and currently recognised under ECTA) or as a sophisticated electronic person (more akin to human-like technology). In doing so, the article explores possible liability structures that could apply to electronic persons in the South African legal framework and concludes that there is a need to update ECTA (and other legislative instruments) so as to recognise and regulate sophisticated automated systems and electronic persons. A failure to do so may mean South Africa is left behind in the wake of technological developments, and may hamper future contractual engagements.